2021
DOI: 10.1097/md.0000000000024264
|View full text |Cite
|
Sign up to set email alerts
|

Association between spiritual well-being, quality of life, anxiety and depression in patients with gynaecological cancer in China

Abstract: The physical and psychological condition of patients with gynaecological cancer has received much attention, but there is little research on spirituality in palliative care. This study aimed to investigate spiritual well-being and its association with quality of life, anxiety and depression in patients with gynaecological cancer. A cross-sectional study was conducted in China in 2019 with 705 patients diagnosed with primary gynaecological cancer. European Organisation for Research and Treatment of Cancer quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
49
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 38 publications
7
49
1
1
Order By: Relevance
“…Given the absence of reports from the other two studies on the scale, “Relationship with God”, mean scores on the “Relationship with Someone or Something Greater” scale from the other two studies are used to compare results from all three studies. The reported values in Rhode (2019) and Chen (2021) (between 50 and 60) [ 27 , 28 ] are considered in the middle range and are lower compared to those reported by our patients (64.6).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Given the absence of reports from the other two studies on the scale, “Relationship with God”, mean scores on the “Relationship with Someone or Something Greater” scale from the other two studies are used to compare results from all three studies. The reported values in Rhode (2019) and Chen (2021) (between 50 and 60) [ 27 , 28 ] are considered in the middle range and are lower compared to those reported by our patients (64.6).…”
Section: Discussioncontrasting
confidence: 73%
“…Two other studies employed the newly developed EORTC-SWB32 tool and reported on levels of spiritual well-being in patients with advanced cancer and its associations with QOL [ 27 , 28 ]. The perceived Global SWB score was high in all three samples (Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spiritual beliefs are often considered as a source for dealing with illness and making decisions on treatment of the patients with chronic illness. Chen et al [ 61 ] showed that spiritual well-being was associated with reduced anxiety and depression. Health care providers need to pay more attention to spiritual care and help cancer patients with spiritual psychological counseling.…”
Section: Discussionmentioning
confidence: 99%